Before the religious right liberal Protestants, human rights, and the polarization of the United States - Zubovich, Gene (Philadelphia University of Pennsylvania Press, 2022)
In the same way that the rise of the New Right cannot be understood apart from the mobilization of evangelicals, Gene Zubovich shows that the rise of American liberalism in the twentieth century cannot be understood without a historical account of the global political mobilization of liberal Protestants.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books